The geoglyph sites of Acre, Brazil: 10 000-year-old land-use practices and climate change in Amazonia. (December 2020) - Pärssinen, Martti; Balée, William; Ranzi, Alceu; Barbosa, Antonia
Abstract: Abstract : Hypotheses concerning climatic change during the Amazonian Holocene often assume that the presence of ancient charcoal from forest fires indicates periods of drier climate in the past. These theories, however, neglect the possibility that such charcoal may result from early human activity. This article presents new evidence of anthropogenic ash and charcoal accumulation in the state of Acre, Brazil, dating back to c . 10 000 cal BP, which questions the value of charcoal as a proxy for phases of natural climate aridification. Carbon isotope (δ 13 C) values also suggest no significant changes in Holocene climate or vegetation. If these results are confirmed, previous studies on Amazonian Holocene climate will require re-evaluation.